The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1136/emermed-2016-206295
|View full text |Cite
|
Sign up to set email alerts
|

Five-level emergency triage systems: variation in assessment of validity

Abstract: Previous studies applied various reference standards and measures to validate five-level triage systems. They either created their own reference standard or used a combination of severity/resource measures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
121
0
11

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 131 publications
(145 citation statements)
references
References 64 publications
(30 reference statements)
1
121
0
11
Order By: Relevance
“…First, we assessed the predictive validity of JTAS using surrogate markers of severity instead of patient acuity. A systematic review suggested that many validation studies of triage systems end up evaluating validity using severity markers, including overall admission and ED length of stay, as was done in our study 19. However, patient acuity and severity are not identical.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…First, we assessed the predictive validity of JTAS using surrogate markers of severity instead of patient acuity. A systematic review suggested that many validation studies of triage systems end up evaluating validity using severity markers, including overall admission and ED length of stay, as was done in our study 19. However, patient acuity and severity are not identical.…”
Section: Discussionmentioning
confidence: 87%
“…A systematic review of five-level triage systems reported that overall admissions and ED length of stay are frequently used outcomes in the studies to validate triage systems 19. Thus, we used overall admission and ED length of stay as the primary outcomes.…”
Section: Methodsmentioning
confidence: 99%
“…A multicentre study conducted in the United States, Brazil and the United Arab Emirates found an overall accuracy of 59.2% and modest inter-rater reliability 4. Not surprisingly, triage systems work better on populations they were developed for 5. A recent review in our pages demonstrated that MTS had sensitivities in the range of 60%–70% for children compared with a reference standard of expert consensus 6.…”
mentioning
confidence: 91%
“…Two papers in this month’s issue of  EMJ systematically examine the validity of triage systems for adults and children1, while Tsai et al analyse the performance of prehospital triage criteria in Taiwan 2. Few emergency physicians have the luxury of being able to see all patients immediately and thus not needing triage.…”
mentioning
confidence: 99%
“…In Kuriyama et al ’s review, a minority of studies address criterion validity, generally using a gold standard of predefined expert consensus on urgency 1. This is pragmatic but possibly not complete; there is little sign of patient and public involvement and as a professional group, we have patchy insight into what our patients might value.…”
mentioning
confidence: 99%